2007
DOI: 10.1074/jbc.m610458200
|View full text |Cite
|
Sign up to set email alerts
|

TrkA Receptor Activation by Nerve Growth Factor Induces Shedding of the p75 Neurotrophin Receptor Followed by Endosomal γ-Secretase-mediated Release of the p75 Intracellular Domain

Abstract: Neurotrophins are trophic factors that regulate important neuronal functions. They bind two unrelated receptors, the Trk family of receptor-tyrosine kinases and the p75 neurotrophin receptor (p75). p75 was recently identified as a new substrate for ␥-secretase-mediated intramembrane proteolysis, generating a p75-derived intracellular domain (p75-ICD) with signaling capabilities. Using PC12 cells as a model, we studied how neurotrophins activate p75 processing and where these events occur in the cell. We demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
82
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(89 citation statements)
references
References 87 publications
7
82
0
Order By: Relevance
“…In contrast, other reports have shown that NGF can induce proteolytic processing of p75 NTR in PC12 cells (35). This effect required activation of TrkA which led to metalloprotease-mediated shedding of p75 NTR and subsequent RIP.…”
Section: Discussionmentioning
confidence: 60%
“…In contrast, other reports have shown that NGF can induce proteolytic processing of p75 NTR in PC12 cells (35). This effect required activation of TrkA which led to metalloprotease-mediated shedding of p75 NTR and subsequent RIP.…”
Section: Discussionmentioning
confidence: 60%
“…Previous studies have shown that some substrates of the γ-secretase complex are endocytosed before cleavage (31,32). We therefore carried out experiments to test whether endocytosis is required for the production of Pcdhα4 CTF1 or CTF2.…”
Section: Resultsmentioning
confidence: 99%
“…p75 expression is also linked to changes occurring in AD (17,29), probably through its direct binding to Abeta 1-42 peptides (29,30). In addition, p75 mediates APP promoter activity, leading to an increase of secreted APP (31,32), and undergoes intramembrane ␣ and ␥ secretase-mediated processing to generate p75 CTF and p75 ICD fragments, respectively (11). Our recent findings have demonstrated a direct link among NGF withdrawal, activation of amyloidogenic pathway, tau processing, and neuronal death (5,6,33), providing evidence for a mechanism in which a discontinued or limited supply of NGF can activate the amyloidogenic pathway, triggering apoptotic death.…”
Section: Discussionmentioning
confidence: 99%
“…Concomitantly with TrkA phosphorylation, the amounts of p75 C-terminal fragments, which are the products of ␣ and ␥ secretase cleavage on p75 (10,11), increase and associate with TrkA to form a molecular complex also including a full length of p75, Abeta peptides, and PS1 protein.…”
mentioning
confidence: 99%